PENERAPAN MEDIA PEMBELAJARAN CONCEPT MAPPING MANDIRI UNTUK MENINGKATKAN HASIL BELAJAR SISWA KELAS XII IPA 6 PADA MATERI SIFAT KOLIGATIF LARUTAN DI SMA NEGERI 1 SUMBER PUCUNG: Concept Mapping Mandiri, Mata Pelajaran Kimia, Media Pembelajaran - Yayuk Wiji Utami (Jurnal Penelitian Multidisiplin, 2022)
Chemistry subject aims to equip students with the ability to think logically, analytically, systematically, critically, and creatively. Chemistry subjects. requires critical thinking for students. This makes the teacher to think creatively. Teacher creativity is needed to develop a learning process that adapts to the circumstances of students and schools. The purpose of this study was to determine the application of independent concept mapping learning media and to know the improvement of student learning outcomes in class XII IPA 6 on the colligative properties of solutions in chemistry subjects at SMA Negeri 1 Sumberpucung. The result of this research is that this research uses classroom action research (CAR). The stages are planning, implementation, observation and reflection. After the implementation of independent concept mapping media, in cycle I and cycle II it showed that concept mapping could improve student learning outcomes for class XII science 6. The percentage of success initially was 70, 37% after the cycle II was carried out, the learning outcomes were 88, 88%. If calculated, it has increased by 18.51%.